Capillary angiogenesis and remodeling induced in rat limb by arteriovenous shunting - Komai, Yutaka; Nakano, Atushi; Niimi, Hideyuki (Clinical hemorheology and microcirculation, 2005)
Capillary angiogenesis and remodeling induced by arteriovenous (AV) shunting in rat hind limb was investigated by evaluating changes in capillary density and diameter in the skeletal muscle subject to retrograde flow and high pressure. Wistar rats were used, and an AV anastomosis was created in the hind limb. Two weeks after AV shunting, the microvasculature in the limb was visualized by GS‐lectine, and the samples were observed using confocal laser microscopy. The capillary density were increased by approximately 150% for small vessels (<13 μm in diameter) under retrograde flow condition, but no change appeared for large vessels (>13 μm in diameter). The capillary diameters were not significantly different between control and chronic condition. In conclusion, retrograde flow produced by AV shunting increased capillary density but it did not change the capillary diameter significantly.